2018
DOI: 10.3171/2018.1.spine171155
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative re-irradiation using stereotactic body radiotherapy for metastatic epidural spinal cord compression

Abstract: OBJECTIVEThis study aimed to clarify the outcomes of postoperative re-irradiation using stereotactic body radiotherapy (SBRT) for metastatic epidural spinal cord compression (MESCC) in the authors’ institution and to identify factors correlated with local control.METHODSCases in which patients with previously irradiated MESCC underwent decompression surgery followed by spine SBRT as re-irradiation between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…Recently, Redmond et al reported results from the first prospective study analyzing post-operative SBRT (30 Gy in 5 fractions), showing 1-year LC of 91.4% [59] . Notably, Ito et al analyzed a retrospective series of 28 patients previously treated with cEBRT, who underwent surgery and subsequent re-irradiation with SBRT (24 Gy in 2 fractions), reporting 1-year LC of 70%, showing SBRT feasibility even for re-irradiation [60] .…”
Section: Evolutions In Radiotherapymentioning
confidence: 99%
“…Recently, Redmond et al reported results from the first prospective study analyzing post-operative SBRT (30 Gy in 5 fractions), showing 1-year LC of 91.4% [59] . Notably, Ito et al analyzed a retrospective series of 28 patients previously treated with cEBRT, who underwent surgery and subsequent re-irradiation with SBRT (24 Gy in 2 fractions), reporting 1-year LC of 70%, showing SBRT feasibility even for re-irradiation [60] .…”
Section: Evolutions In Radiotherapymentioning
confidence: 99%
“…A total of 461 patients and 499 segments treated across 12 studies were included in this analysis. [14][15][16][17][18][19][20][21][22][23][24][25] Surgical techniques were heterogenous, and a description of technique used per study is outlined in Table 2. Seven studies were retrospective by design, two were prospective observational and three were prospective phase I/II clinical trials.…”
Section: Resultsmentioning
confidence: 99%
“…The median time interval between surgery and SBRT was reported by five of the included studies and ranged from 14 days to 45 days. [14][15][16]21,22 Two studies reported the mean time as 14 days and 44 days, and a further two investigators treated patients within 2 months and 4 months, respectively. 19,20,23,24 The two studies that reported a median and mean time of 14 days were investigations of MIS and percutaneous treatment of vertebral body tumors, respectively.…”
Section: Impact On Wound Healing and Time Interval Between Surgery And Sbrtmentioning
confidence: 99%
“…Regarding dose fractionation in radiotherapy, while single irradiation is said to maintain motor function and bladder function at the same level as multiple irradiations, some reports indicate that higher doses provide a higher local control rate. In recent years, stereotactic radiotherapy (SRT) is also being used [5,12]. Moulding HD et al studied 21 patients who underwent SRT after spinal decompression and fixation and reported that 24 Gy/1 fraction controlled the tumor regardless of the tumor's radiation sensitivity [5].…”
Section: Discussionmentioning
confidence: 99%